2010
DOI: 10.1152/ajpgi.00237.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptional characteristics of small and large biliary epithelial cells derived from small and large bile ducts

Abstract: Biliary epithelial cells (BEC) are morphologically and functionally heterogeneous. To investigate the molecular mechanism for their diversities, we test the hypothesis that large and small BEC have disparity in their target gene response to their transcriptional regulator, the biliary cell-enriched hepatocyte nuclear factor HNF6. The expression of the major HNF (HNF6, OC2, HNF1b, HNF1a, HNF4a, C/EBPb, and Foxa2) and representative biliary transport target genes that are HNF dependent were compared between SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
(62 reference statements)
1
23
0
Order By: Relevance
“…Primer sequences are listed in Table 1. Hnf6 , Hnf1b , Hnf4a , Oc2 , Foxa2 , C/epb primer sequences have been reported previously [6,15,17]. Relative gene expression was calculated using the mathematical delta delta method by PE Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences are listed in Table 1. Hnf6 , Hnf1b , Hnf4a , Oc2 , Foxa2 , C/epb primer sequences have been reported previously [6,15,17]. Relative gene expression was calculated using the mathematical delta delta method by PE Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…Large cholangiocytes are thought to produce the majority of bile, while the rest (10–30%) is produced by the hepatocytes in rats and humans respectively [35,36]. However, it has been demonstrated that both small and large cholangiocytes express bile acid transporters (e.g., sodium/taurocholate co -transporting polypeptide [ ntcp ], organic anion-transporting polypeptide [ oatp1 ] and multidrug resistance protein 2 [ mrp2 ]) and aquaporins, suggesting that both may play a substantive role in bile acid transport and production [37,38]. Regardless, it is clear that the apical and basolateral membranes of large cholangiocytes possess specialized functions via the presence of different ion carriers and channels (Fig.…”
Section: Normal Cholangiocyte Structure and Functionmentioning
confidence: 99%
“…Recent observations, however, suggest that the functional heterogeneity of large and small cholangiocytes is more complex, and that both large as well as small cholangiocytes may contribute to bile modification (106,283). …”
Section: Overview Of Ductal Architecture and Developmental Originmentioning
confidence: 99%